Words Operation Strategy and Analysis of Tencent Video’s Homemade Drama - Wang, Ning; Yu, Ruhao; Zhou, Feihan; Zang, Yunqi (Transactions on Economics, Business and Management Research, 2024)
The rise of self-produced dramas on video platforms is a major trend in the Chinese online video industry in recent years. Tencent Video, as one of the leading online video platforms in China, has successfully attracted a large number of users through substantial investment in self-produced dramas and has stood out in the market competition. This paper aims to conduct an in-depth study on the operational strategies and analysis of self-produced dramas on Tencent Video. By collecting and analyzing relevant data on self-produced dramas on the Tencent Video platform, it explores metrics for measuring the popularity of self-produced dramas and the impact of content innovation on user attraction. The research methods include data collection and analysis, as well as comparative analysis of the operational strategies of different self-produced dramas. The main point of this paper is to emphasize the importance of operational strategies for self-produced dramas and provide operational strategy recommendations for Tencent Video’s self-produced dramas. The research findings will provide practical guidance on the operation of self-produced dramas for video platforms, promote the development of the self-produced drama industry, enhance user satisfaction, and drive the sustainable development of video platforms.